Effects of the utilization of a local cereals and forage -based diet on productive performance and egg quality in three free-range hen genotypes - Serezade Sigut; Sergio Álvarez; María Fresno; Pilar Méndez; Noemi Castro; Alexandr Torres (Journal of Applied Poultry Research)
Summary: Meeting consumer demand for eggs is dependent to a major extent on the availability of regular supplies of appropriate, cost-effective and safe animal feeds. Greater utilization of local feedstuffs, such as cereals and forages, is being encouraged for small and medium-sized poultry farmers for increasing poultry production, and enhancing food security. This research paper addresses the effects of a diet based on local cereals and forage on productive performance and egg quality in three hen genotypes (Lohmann White, Canarian, and Franciscana) reared under free-range conditions during 16 weeks. The results showed that hens fed with the commercial formula exhibited better body weights, laying rates, feed conversion ratios, and laid heavier eggs than the hens fed with the experimental diet. On the other hand, yolk color of hens fed with local cereals and forage were paler and less red and yellow than those fed with a commercial layer feed. Nevertheless, chemical composition and fatty acids profile of egg yolks were not altered by the diet factor. Finally, untrained consumers pointed out that the control eggs had a better score in terms of external and internal assessments than experimental eggs, but did not find differences for aroma and taste. In conclusion, it seems clear the need to introduce changes in the formulation of the local diet that may improve the productive performance and the quality of the eggs. This improvement must be consolidated by incorporating external amino acids, pigments and enzymes.